PENINGKATAN KEMAMPUAN BERPIKIR LOGIS MELALUI PENERAPAN DISCOVERY LEARNING PADA MATERI SISTEM REPRODUKSIDI KELAS XI MIA 1 SMA BATIK 2 SURAKARTA TAHUN PELAJARAN 2014/2015 - Sondra Swestyani; Yudi Rinanto; Sri Widoretno (Universitas Sebelas Maret, 2016)
This research was aimed to improve the students' logical thinking in XI MIA 1 of SMA Batik 2 Surakarta Academic Year 2014/2015 about reproduction system material through discovery learning application.This research was a class action research which consisted of three cycles. Each cycle contains planning, implementing, observing and reflecting. The research subject was the students in XI MIA 1 of SMA Batik 2 Surakarta Academic Year 2014/2015. The data source was from the mind map that cover the logical thinking aspects. Data collecting techniques of this research used observation, interview and documentation then data validation was using triangulation method. Data analyzing technique of this research was descriptive qualitative analysis which was done in three components, they are: data reduction, data presentation and drawing the conclusion or verification. The research’ procedure used spiral mode which is interdependent. The result of the research showed that the implementation of discovery learning improves the students’ logical thinking that covers aspects of knowledge, comunication, thinking, and application. The persentage of knowledge aspect was 53,23% in pre cycle, 81,04% in first cycle , 89,11%, in second cycle, and 95,16% in third cycle . The persentage of comunication aspect was 28,33% in pre cycle, 35,08% in first cycle, 67,74% in second cycle, and 71,77% in third cycle. The persentage of thinking aspect was 28,33% in pre cycle, 58,87% in first cycle, 49,19% in second cycle, and 73,39% in third cycle. Then the persentage of knowledge aspect was 41,53% in pre cycle, 72,18% in first cycle, 79,03% in second cycle, and 77,42% in third cycle. This research’s conclusion was the implementation of discovery learning can improve the students’ logical thinking in X MIA 1 of SMA Batik 2 Surakarta academic Year 2014/2015 about reproduction system material. Keywords :discovery learning, logical thinking